The Morehouse mystique : becoming a doctor at the nation's newest African American medical school - Gasman, Marybeth (Johns Hopkins University Press, 2012)
Tells the history of the Morehouse School of Medicine, situating the school in the context of the history of medical education for Blacks and race relations throughout the country. --From publisher description.